Cross-border mergers and acquisitions : the case of merger control v. merger deregulation - Bedier, Mohammad El-Saied (Edward Elgar Publishing, 2018)
This book demystifies the dynamics of cross-border mergers and acquisitions; from the preliminary agreements and due diligence, to valuation, structuring, financing, and the eventual closing of the deal. It examines merger incentives and efficiencies, in theory and in empirical findings. The author adeptly identifies the impediments facing cross-border mergers and acquisitions and focuses on pre-merger control laws and regulations, particularly those of the US, EU, and Middle East. Consideration is also given to merger deregulation and other key reforming proposals. The book will be a useful resource for students and scholars with an interest in mergers and acquisitions, antitrust laws, and corporate history. Legal Professionals and those in related fields will gain a practical understanding of how to tailor their deals to overcome the unique impediments associated with cross-border transactions. Policy makers will also find the information and assessment criteria developed in the book to be a useful tool for evaluating and designing policy.